2011
DOI: 10.1371/journal.ppat.1002436
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Activating KIR Copy Number Variation of NK Cells with Containment of SIV Replication in Rhesus Monkeys

Abstract: While the contribution of CD8+ cytotoxic T lymphocytes to early containment of HIV-1 spread is well established, a role for NK cells in controlling HIV-1 replication during primary infection has been uncertain. The highly polymorphic family of KIR molecules expressed on NK cells can inhibit or activate these effector cells and might therefore modulate their activity against HIV-1-infected cells. In the present study, we investigated copy number variation in KIR3DH loci encoding the only activating KIR receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…More recently, the KIR gene dose was associated with simian immunodeficiency virus and HIV-1 viral load in rhesus macaque and humans, respectively, suggesting that KIR gene copy number variation (CNV) influences antiviral immunity. 2,3 One suggested mechanism for how the KIR gene CNV affects the NK cell response to viral infection is by promoting education. 3 During NK cell education, interactions between inhibitory KIRs and their cognate HLA class I ligands set the threshold for NK cell activation upon stimulation with target cells lacking the corresponding HLA class I ligands.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the KIR gene dose was associated with simian immunodeficiency virus and HIV-1 viral load in rhesus macaque and humans, respectively, suggesting that KIR gene copy number variation (CNV) influences antiviral immunity. 2,3 One suggested mechanism for how the KIR gene CNV affects the NK cell response to viral infection is by promoting education. 3 During NK cell education, interactions between inhibitory KIRs and their cognate HLA class I ligands set the threshold for NK cell activation upon stimulation with target cells lacking the corresponding HLA class I ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In that report, we demonstrated that copy number variation (CNV) of the activating KIR3DH gene family was associated with lower simian immunodeficiency virus (SIV) replication during acute SIV infection in Mamu-A*01 Ϫ Indian-origin rhesus macaques that express restrictive TRIM5 alleles (11). In the present studies, we demonstrate an association between CNV of the other known activating KIR gene family in Indian-origin rhesus macaques, KIR2DL4 (12)(13)(14)(15)(16), and the loss of CD4 ϩ T cells in acutely SIVmac251-infected Mamu-A*01 Ϫ rhesus macaques, with higher KIR2DL4 copy numbers being associated with a less severe CD4 ϩ T-cell depletion.…”
mentioning
confidence: 99%
“…We used a qPCR assay that recognized a conserved region of the KIR3DH genes that encodes the transmembrane domain of the KIR3DH proteins to determine KIR3DH copy numbers. In addition, we used this assay to quantify the expression of KIR3DH alleles that contain a transmembrane domain, molecules that are likely to be expressed on the surface of the NK cell, and we have previously shown that higher KIR3DH copy numbers were positively associated with higher KIR3DH transcript levels (8). Higher KIR3DH copy numbers therefore likely result in increased surface expression of KIR3DH on subpopulations of NK cells, as reported for the activating KIR3DS1 in humans (12,16).…”
mentioning
confidence: 97%
“…The simian immunodeficiency virus (SIV)-infected rhesus monkey provides an important nonhuman primate animal model for studying NK cell biology during a primary AIDS virus infection. We have recently demonstrated an association between specific NK cell subpopulations and the early containment of SIV replication in rhesus monkeys and a contribution of activating KIRs in stimulating NK cells to control the spread of SIV (8). In that study, we evaluated copy number variation (CNV) of KIR3DH, which represents an activating KIR receptor family in rhesus monkeys (4,9), and showed that KIR3DH copy numbers were negatively associated with SIV replication at the time of the early peak of viral replication in Mamu-A*01 Ϫ rhesus monkeys that express restrictive TRIM5 alleles.…”
mentioning
confidence: 99%
See 1 more Smart Citation